JURI OPI (OLIMPIADE PELITA INDONESIA) MAGIC 5.0 INSTITUT BISNIS DAN TEKNOLOGI PELITA INDONESIA - Irman, Mimelientesa; Anton, Anton; Yusrizal, Yusrizal; Suharti, Suharti; Fadrul, Fadrul (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The form of this activity is OPI (Indonesian Pelita Olympics) Magic 5.0 at the Pelita Indonesia Institute of Business and Technology which was organized by BEM IBT Pelita Indonesia with the theme